REKONSTRUKSI LAPORAN KEUANGAN BERDASARKAN SAK EMKM STUDI KASUS PADA UD. TANJUNG JAYA SITUBONDO - Ansori, Ahmad Faisol; Probowulan, Diyah; Martiana, Nina (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
SAK EMKM is intended for use by small and medium entities, namely entities that do not have significant public accountability or based on laws and regulations are classified as small and medium entities. Qualitative research method with descriptive analysis approach. The results of the study show that the registration is still being carried out by UD. Tanjung Jaya is still fairly simple and manual, that is, financial records at the company only use recorded notes. Recording is done only to record cash receipts from sales and income and cash disbursements such as purchases of merchandise and expenses. For the preparation and presentation of financial statements based on SAK EMKM starting from collecting evidence of transactions, journalizing, ledgers, trial balance, then preparing financial reports, namely statements of financial position, income statements and notes on financial statements.